COVID-19 Impact on Household Water-Energy-Food Accessibility Concerning Achieving the Sustainable Development Goals in Cities and Societies of Northern Nigeria - Yahaya Sani (Journal of the Knowledge Economy, 2025)
The recent COVID-19 pandemic has considerably impacted negatively on many aspects of human life such as access to basic necessities including water, energy and food. This article aims to investigate the impact of the COVID-19 lockdown on the water, energy and food accessibility in Katsina state, Nigeria. The survey involved the administration of a questionnaire to a total of 900 households out of which 66.7% representing 600 urban households and 33.3% are linked to 300 households of the rural sampled households. The null hypothesis (H0) was that there was no significant influence of the COVID-19 pandemic on the water, energy and food security concerning households. A paired t-test analysed the statistical mean of the water-energy-food accessibility under two scenarios (i.e. pre-COVID-19 and post-COVID-19 lockdown). The investigation found that the lockdown measures introduced to control the spread of COVID-19 had a significant influence on the accessibility of water, energy and food. Results revealed that admission to safely managed water provisions dropped from 30.0 to 24.6% across the scenarios. The electricity index access has also reduced from 1.9 to 1.5. Additionally, households that experience severe food insecurity have significantly increased from 4.9 to 38.6% during the pre- and post-COVID-19 lockdown, respectively. Concerning the investigated households for both the urban and rural strata, the investigation highlights the need for policy intervention to ensure that vulnerable households are not disproportionately affected during crises such as a pandemic. The findings will be useful to policymaking and will advance awareness towards achieving the sustainable development goals (SDG).
Keywords: 330; COVID-19 pandemic; Electricity index; Lockdown; Resilient society; Resource accessibility; Water; energy and food nexus